ANALISIS KETERSEDIAAN DAN KONDISI MEDIA PEMBELAJARAN IPA PADA KELAS TINGGI SEKOLAH DASAR DI KECAMATAN CILEUNYI, KABUPATEN BANDUNG - Roni Wahyu Wandani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to examine the state and accessibility of science education materials in upper-grade elementary school classrooms in Bandung Regency's Cileunyi District. 35 upper-grade teachers from 24 elementary schools—18 public and 6 private—participated in the study, which used a quantitative descriptive methodology. A 4-point Likert scale questionnaire was used to collect data between May and July of 2026. Aspects of science learning media availability and condition, including media completeness, maintenance, storage facilities, and staff in charge of media checks, were taken into consideration when developing the study instrument. Descriptive statistics were used to assess the data by computing score achievement percentages and categorizing the results. The findings show that, with an achievement level of 61.67%, the availability of science learning materials falls into the